WARAK NGENDOG DALAM TRADISI DUGDERAN SEBAGAI REPRESENTASI IDENTITAS MUSLIM URBAN DI KOTA SEMARANG - Cahyono Cahyono (Jurnal Theologia, 2018)
This research aims to explore how Warak Ngendog in the Dugderan tradition represents the identity of urban Muslim communities in the city of Semarang. This research also aims to expose the strength of the city's Muslim culture that has been maintained to this day. This study uses an identity theory approach by Peter J. Burke and Homi K. Bhabha about Hybrid culture, and several other extraordinary theories as supporting theories. This research uses a qualitative descriptive approach with the support of substantive information from archives and interviews with related figures. The results of this study emphasize that the dynamics of the religiosity of urban Muslim communities in Semarang City shape urban Muslim identity. Acculturation of the traditional culture of Javanese, Arab, and Chinese Muslims symbolizes the new religious and cultural rites as an inseparable part of the urban Muslim identity of Semarang City because there are social interactions in their involvement in religious rituals, traditions and culture.